Novel inhibitors of the Staphylococcus aureus quorum sensing system - Jaiyen, Yanin (2017)
The recent rise of antibiotic resistant micro-organisms has led to an increased demand for the production of novel and effective antimicrobial therapies. Staphylococcus aureus is a Gram positive human pathogen that some clinical isolate has evolved resistance to all currently available ‘front line’ antibiotics. In this study a series of small molecules, both natural and synthetic, were assessed for their ability to inhibit S. aureus virulence factor production, in the hope to identify novel molecules that inhibit S. aureus pathogenicity. Such molecules have the advantage over classical antibiotics in that they do not generate a selective pressure that can cause the evolution of drug resistant strains. IQS (Integrated Quorum Sensing Signal, 2-(2-hydroxyphenyl)-thiazole-4-carbaldehyde), is a secondary metabolite produced by Pseudomonas aeruginosa that has been suggested to function as a quorum sensing signal molecule. Here, IQS was found to inhibit S. aureus exotoxin production. In an attempt to improve potency, a small library of structurally diverse IQS analogues was synthesised. Two analogues were shown to have increased potency relative to natural IQS. Interestingly, data suggest that the active analogues, which are structurally distinct, have a different mechanism of action. The use of both in vivo reporters and biochemical analysis with purified AgrA, the response regulator that transduces the S. aureus QS signal, suggested that the lead analogue (IQS3) binds to and disrupts the DNA binding of AgrA, thus inhibiting QS by S. aureus. RNAseq data support the biochemical analysis in that the expression of virulence genes by S. aureus treated with the lead analogue mirrors that an S. aureus QS mutant. Finally, the cytotoxicity of our lead analogues were assessed. Overall, data suggest that our lead IQS analogue is a good ‘starter’ molecule for further modification in the hope to increase anti-virulence properties whilst reducing cytotoxicity.